PERAN MAJLIS TA’LIM ASSAKINNAH BIDAYATUS SALAM DALAM MENINGKATKAN SPIRITUALITAS DAN RELIGIUSITAS MASYARAKAT DESA KETRO KECAMATAN TULAKAN PACITAN - Juminto Juminto; Happy Susanto; Nuraini Nuraini (Universitas Muhammadiyah Ponorogo, 2020)
The purposes of this research are; (1) to explains the education of majlis ta’lim Assakinnah Bidayatus salam in improving spirituality and religiosity . (2) to explain the efforts of majlis ta’lim Bidayatus salam in improving spirituality and religiosity(3) to explain the implication of majlis ta’lim Assakinnah Bidayatus salam in enhancing spirituality and religiosity. the research method used in this study is qualitative approach. Date collection method used were interview observation and document. This research result indicates that the implementation of majlis ta’lim Assakinnah Bidayatus salam according to conditional of those pilgrims, there were a learning contract between presenters and learning pilgrims with various materials as aqidah, fiqih, fiqih munakahat, also qur’an and hadits/plantation and agriculture. With spirituality that is before the majlis ta’lim strengthens faith and aqidah, sakinah education, empower the poor, the development and implementation of da’wah. While from religiosity of the efforts made by majlis ta’lim is a good example, the movement of prayer , reciting the Qur’an together and an it is together. The implication of the spirituality and religiosity for pilgrims/comunity in increasing the value of rituals in carrying out obligations, the growth of social attitudes , and mutual cooperate to help and and intellectual developmentof the community.